2019
DOI: 10.1155/2019/6808062
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Safety and Stability in Cases of Small Incision Lenticule Extraction with Collagen Cross-Linking (SMILE Xtra)

Abstract: Purpose. To assess the safety and stability in cases of small incision lenticule extraction with collagen cross-linking (SMILE Xtra). Methods. This study was a retrospective interventional comparative study that included 60 eyes of 30 patients divided equally into two groups: SMILE Xtra and SMILE alone. The inclusion criteria were patients >18 years of age, myopic error >6 D, thinner cornea <520 microns, and abnormal corneal topography. Outcome data were recorded including uncorrected distance visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 31 publications
(36 reference statements)
3
28
0
Order By: Relevance
“…Another study 40 indicated that corneal resistance factor (CRF) was higher in the SMILE Xtra group in the postoperative period, but significantly lower than the preoperative levels. Tomita et al 51 reported the mean preoperative and postoperative change in all dynamic bidirectional applanation device parameters 3, 6 and 12 months postoperatively.…”
Section: Corneal Biomechanicsmentioning
confidence: 97%
See 4 more Smart Citations
“…Another study 40 indicated that corneal resistance factor (CRF) was higher in the SMILE Xtra group in the postoperative period, but significantly lower than the preoperative levels. Tomita et al 51 reported the mean preoperative and postoperative change in all dynamic bidirectional applanation device parameters 3, 6 and 12 months postoperatively.…”
Section: Corneal Biomechanicsmentioning
confidence: 97%
“…Overall, there were no statistically significant differences between LASIK-only eyes and LASIK-CXL eyes. Another study 40 indicated that corneal resistance factor (CRF) was higher in the SMILE Xtra group in the postoperative period, but significantly lower than the preoperative levels.…”
Section: Corneal Biomechanicsmentioning
confidence: 97%
See 3 more Smart Citations